Coastal Freshening Prevents Fjord Bottom Water Renewal in Northeast Greenland: A Mooring Study From 2003 to 2015. Issue 6 (23rd March 2018) - Boone, Wieter; Rysgaard, Søren; Carlson, Daniel F.; Meire, Lorenz; Kirillov, Sergei; Mortensen, John; Dmitrenko, Igor; Vergeynst, Leendert; Sejr, Mikael K.
Abstract: The freshwater content of the Arctic Ocean and its bordering seas has recently increased. Observing freshening events is an important step toward identifying the drivers and understanding the effects of freshening on ocean circulation and marine ecosystems. Here we present a 13 year (2003–2015) record of temperature and salinity in Young Sound‐Tyrolerfjord (74°N) in Northeast Greenland. Our observations show that strong freshening occurred from August 2005 to August 2007 (−0.92 psu or −0.46 psu yr −1 ) and from August 2009 to August 2013 (−0.66 psu or −0.17 psu yr −1 ). Furthermore, temperature‐salinity analysis from 2004 to 2014 shows that freshening of the coastal water ( range at sill depth: 33.3 psu in 2005 to 31.4 psu in 2007) prevented renewal of the fjord's bottom water. These data provide critical observations of interannual freshening rates in a remote fjord in Greenland and in the adjacent coastal waters and show that coastal freshening impacts the fjord hydrography, which may impact the ecosystem dynamics in the long term. Plain Language Summary: The freshwater content of the Arctic Ocean has increased in recent years in response to climate change, but the impact of freshening on coastal ecosystems, such as fjords, is largely unknown. Freshening is important, as the related change in density can weaken vertical mixing and, subsequently, slow or stop the renewal of the fjord bottom water. Analysis of long‐term data (2003–2015) near Young Sound‐Tyrolerfjord, a high Arctic fjord in Northeast Greenland, identified anomalously strong freshening events that are at the high end in comparison to other freshening estimates from around the Arctic. Furthermore, the data reveals that renewal of the bottom water was prevented by freshening of the coastal water since 2004–2005. This shift toward fresher coastal water, in combination with freshening of the fjord's basin water, may impact the fjord's ecosystem functioning in the long term. The observations in this study provide new insights into the temporal variability of salinity and temperature and thus provide a critical step toward an impact assessment and identification of underlying processes driving freshening in Northeast Greenland. Key Points: Thirteen‐year continuous time series demonstrate an overall freshening trend but show seasonal and interannual variability Freshening was anomalously high from August 2005 to August 2007 (−0.92 psu or −0.46 psu yr −1 ) and from August 2009 to August 2013 (−0.66 psu or −0.17 psu yr −1 ) Reduced density within the fjord was compensated by a stronger density decrease in the coastal water, which prevented bottom water renewal